Efficacy and In Vitro Cytotoxicity of Nanostructured Lipid Carriers for Paclitaxel Delivery - Shady Ali Swidan , , Hassan Mahmoud Ghonaim, Ahmed Mahmoud Samy, Mamdouh Mostafa Ghorab (Journal of Applied Pharmaceutical Science, 2016)
Paclitaxel (PTX) is an anticancer drug having poor aqueous solubility and low bioavailability. Formulation of PTX into Nanostructure lipid carriers (NLC) could be a potential way to enhance PTX aqueous solubility and bioavailability hence increases efficacy and decreases side effects. Eight PTX-NLC formulae were prepared using homogenization-ultrasonication technique. Characterization of the nanoparticles was done by transmission electron microscopy and by measurement of particle size, poly dispersibility index and zeta potential. Encapsulation efficiency, drug loading, and In Vitro release were measured. Particle size ranged between 172.8 ± 0.8 to 378.2 ± 1.8 nm and zeta potential between -18.6 ± 0.4 to -28.1 ± 1.2 mV. High EE and DL were obtained due to incorporation of liquid lipid and the In Vitro release showed prolonged time dependent release compared to Taxol®. NLC-3 had the best results among the eight prepared formulae. In Vitro cytotoxicity of NLC-3 was evaluated on MCF-7 cell line and compared to pure PTX powder and Taxol®. These findings show that NLC is a potential carrier to improve efficacy and enhance PTX delivery.
Keywords: Nanostructured lipid carriers, Capryol 90, Paclitaxel, Cytotoxicity, MCF7.